THYROID SURGERY: DRAIN VERSUS NO DRAIN - Nawaz, Saadia; Naeem, Amjad; zeb, Ahmed (Journal of Postgraduate Medical Institute, 2015)
Objective: To compare patients undergoing thyroid surgery without the placement of a drain versus patients undergoing surgery with placement of drain; in terms of hospital stay, operative pain score, amount of fluid collection in the neck and postoperative complications. Methodology: This study was conducted at surgical unit, Naseer Teaching Hospital, Peshawar from January 2010 to July 2014. Important variables ofthe study were duration of hospital stay, post operative pain score, amountof fluid collection in the wound as detected on ultrasound and postoperative complications. Visual Analogue scale was used to assess postoperative pain on completion of 24 hours. All the patients were subjected to ultrasound of the neck on the 1st post-operative day. The data was entered on a proforma and analyzed on SPSS 21. Results: The study included 68 patients; being grouped in to two groups the group with drain showed no difference demographically from the group in which drain was not placed post operatively. Mean postoperative pain score24 hours after surgery was 60.87± 7.06 SD in the drain group and 41.19± 4.18SD in no drain group (p value < 0.05). Mean duration of hospital stay was 3.63days ± 0.707 SD in drain group and 1.19 days ± 2.145 SD in no drain group(p value <0.05). Conclusion: "Drain less" Thyroidectomy causes less discomfort, short hospital stay and does not increase the risk of post operative complications. Drains should be used only in selected cases of Thyroidectomy.